Effect of Insect Pollination on the Yield of Sesamum Indicum (Pedaliaceae) in Maroua-Cameroon - Pando, Joseph Blaise; Djonwangwé, Denis; Moudelsia, Olivier Balti; Fohouo, Fernand-Nestor Tchuenguem; Tamesse, Joseph Lebel (JOURNAL OF ADVANCES IN AGRICULTURE, 2020)
From July to October 2015 and 2018 at Maroua, Sesamum indicum flowers were observed to determine the reproductive system, specific richness, relative frequency, and impact of the insects on the yields. 7800 and 4560 flower clusters for each studied were labeled and divided into two treatments, differentiated according to the presence or absence of protection against insect’s activities. Observations were made on free-pollinated S. indicum flowers from September to October 2015 and 2018. The sesame is a mixed pollination plant, and the specific richness of the flowering insects was 19 species. The insects foraged the flowers of the sesame from 7:00 am to 4:00 pm, with the peak of the activity of the set of visits of them located between 9:00 am, and 10:00 am (28.59 %). These insects developed and elaborated behavior when they collected the nectar and pollen. Free-pollination produced more yield than pollination restricted with gauze bags. The influence of the insects estimated at 50.84 %, 17.22 %, 58.77 %, and 09.55 % for the fruiting rate, the number of seeds/fruit, the percentage of the average weight of seeds, and the percentage of normal seeds respectively. This study provided some knowledge about the insect’s diversity of this Pedaliaceae, which can be exploited to improve fruit production. In order to improve the yield of S. indicum, pollinators could be protected by rational pest management tactics. Pesticide treatments should be done in the late afternoon to protect the pollinators for high seed yield or spray at a time of day when crop flowers are closed.